The Effect of Information Technology on Fluidity of Contemporary Architectural Space - Shatha Abbas Hassan; Noor Ali Aljorani (Wasit Journal of Engineering Sciences)
The increasing importance of the information revolution and terms such as ‘speed’, ‘disorientation’, and ‘changing the concept of distance’, has provided us with tools that had not been previously available. Technological developments are moving toward Fluidity, which was previously unknown and cannot be understood through modern tools. With acceleration of the rhythm in the age we live in and the clarity of the role of information technology in our lives, as also the ease of access to information, has helped us to overcome many difficulties. Technology in all its forms has had a clear impact on all areas of daily life, and it has a clear impact on human thought in general, and the architectural space in particular, where the architecture moves from narrow spaces and is limited to new spaces known as the ‘breadth’, and forms of unlimited and stability to spaces characterized with fluidity. The research problem (the lack of clarity of knowledge about the impact of vast information flow associated with the technology of the age in the occurrence of liquidity in contemporary architectural space) is presented here. The research aims at defining fluidity and clarifying the effect of information technology on the changing characteristics of architectural space from solidity to fluidity. The research follows the analytical approach in tracking the concept of fluidity in physics and sociology to define this concept and then to explain the effect of Information Technology (IT) to achieve the fluidity of contemporary architectural space, leading to an analysis of the Skidmore, Owings and Merrill (SOM) architectural model. The research concludes that information technology achieves fluidity through various tools (communication systems, computers, automation, and artificial intelligence). It has changed the characteristics of contemporary architectural space and made it behave like an organism, through using smart material.